Progress of immune checkpoint inhibitors in the treatment of advanced hepatocellular carcinoma - Liu, Tong; Meng, Guorui; Ma, Shihui; You, Junqi; Yu, Liang; He, Risheng; Zhao, Xudong; Cui, Yunfu (Frontiers in Immunology, 2024)
Among primary liver cancers, hepatocellular carcinoma is the most common pathological type. Its onset is insidious, and most patients have no obvious discomfort in the early stage, so it is found late, and the opportunity for surgical radical treatment is lost, resulting in a poor prognosis. With the introduction of molecular-targeted drugs represented by sorafenib, patients with middle-and late-stage liver cancer have regained the light of day. However, their therapeutic efficacy is relatively low due to the limited target of drug action, toxic side effects, and other reasons. At this time, the emergence of immunotherapy represented by immune checkpoint inhibitors (ICIs) well breaks this embarrassing situation, which mainly achieves the anti-tumor purpose by improving the tumor immune microenvironment. Currently, ICI monotherapy, as well as combination therapy, has been widely used in the clinic, further prolonging the survival of patients with advanced hepatocellular carcinoma. This article reviews the development of monotherapy and combination therapy for ICIs in advanced hepatocellular carcinoma and the latest research progress.